Analisis Kerugian Ekonomi Masyarakat Akibat Banjir di Kelurahan Kampung Salo Kecamatan Kendari Kota Kendari - Ririn Pabutungan; Safril Kasim; La Ode Midi (PT. Hasba Edukasi Mandiri, 2026)
Flood disaster is an event or situation where an area or land is submerged due to an increase in water volume. The purpose of this study is to determine the value of direct and indirect economic losses suffered by the community due to flooding in Kampung Salo Village, Kendari District, Kendari City. This research was conducted in Kampung Salo Village, Kendari District, Kendari City from March to April 2025. Data collection methods included observation, interviews, and literature study. Data analysis was carried out by distinguishing between direct and indirect economic losses. Direct economic losses were analyzed through the calculation of costs related to the loss of household furniture and replacement costs for repairing furniture, vehicles, and buildings. Meanwhile, indirect economic losses were analyzed based on medical/hospitalization costs, lost income, and additional expenses. The results indicate that the flooding caused significant economic losses to the affected community. The economic loss value was calculated based on direct losses, including damage and loss of economic assets such as household furniture, replacement costs for repairing furniture, vehicles, and buildings, and indirect losses, including medical/hospitalization costs, lost income, and additional expenses. The total estimated economic loss experienced by the affected community in Kampung Salo Village, Kendari District, Kendari City is Rp7.086.939.975,36. The largest portion of the losses came from direct economic losses amounting to Rp4.215.526.453,44, followed by indirect losses totaling Rp2.871.413.521,92. Efforts made by the government to reduce the impact of flooding include the development of drainage systems, such as cleaning drainage channels and repairing river embankments